(untitled) (Journal Of Educational and Psychological Researches, 2014)
Quite anumber of parents and educators of this behavior,which is characterized by exaggerating locomotor activity and impulsivity and recklessness and the difficulty of continuing the status of certain bodily more than one minute ,and the difficulty of waiting to meet aparticular need or desire,it also characterized by thos meddling children the affairs of others and increased their chatter does not seem the case when you listen to talk to them and they characterized by weak self-confidence and are more solid and seem un able to keep ther responses because of the severity of anxiety .The research aims to know impulsive behavior among kindergartens children and its relation ship with some variables, and the sample consisted of 400 child from kindergartens in the city of Baghdad in both of (Karkh and Rusafa) The research also Checks the psychometric standard properties of the scale honesty , fortitude and honesty was verified in two ways honesty and sincerity of virtual construction , extraction was consistency in two ways retesting and Alnakronbach . And The research found the following results 1-The emergence of implusive behavior in children of the age of stag (6-4years). • There are no statistically significant differences in impulsive behavior among children variable(4-5)(5-6)years. • There are statistically significant differences in impulsive behavior among kindergartens children by variable and in favor of the male sex.